2019
DOI: 10.1016/s2095-3119(18)62130-6
|View full text |Cite
|
Sign up to set email alerts
|

Overhead supplemental far-red light stimulates tomato growth under intra-canopy lighting with LEDs

Abstract: Far-red (FR) light regulates phytochrome-mediated morphological and physiological plant responses. This study aims to investigate how greenhouse tomato morphology and production response to different durations of FR light during daytime and at the end of day (EOD). High-wire tomato plants were grown under intra-canopy lighting consisting of red (peak wavelength at 640 nm) and blue (peak wavelength at 450 nm) light-emitting diodes (LEDs) with photosynthetic photon flux density (PPFD) of 144 μmol m-2 s-1 at 10 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 26 publications
9
58
1
Order By: Relevance
“…This is in accordance to study of Park and Runkle (2017) on snapdragon and geranium under R:B with FR that could increase shoot dry weight by 28-50%. This is further confirmed by Zhang et al (2019) who provided the study results that the R:B LED (R 640 nm, B 450 nm) in combination with FR (735 nm) at 43 μmolm -2 sec -1 could increase the total plant biomass of high-wire tomato plants by 16% better than sole R:B LED (Zhang et al, 2019). Meng and Runkle (2017) reported that the B and R did not influence the biomass of basil.…”
Section: Holy Basilmentioning
confidence: 58%
See 4 more Smart Citations
“…This is in accordance to study of Park and Runkle (2017) on snapdragon and geranium under R:B with FR that could increase shoot dry weight by 28-50%. This is further confirmed by Zhang et al (2019) who provided the study results that the R:B LED (R 640 nm, B 450 nm) in combination with FR (735 nm) at 43 μmolm -2 sec -1 could increase the total plant biomass of high-wire tomato plants by 16% better than sole R:B LED (Zhang et al, 2019). Meng and Runkle (2017) reported that the B and R did not influence the biomass of basil.…”
Section: Holy Basilmentioning
confidence: 58%
“…The holy basil under R:B.3.5+FR50 increased the average leaf number by 295 and 64% of R:B.3.5 and R:B.7 and increased average leaf area by 89% of R:B.3.5 and 59% of R:B.7. FR light clearly indicated the leaf morphological development, FR light (735 nm) at 43 μmolm -2 sec -1 with R:B produce larger leaf area of tomato when compared to R:B without FR (Zhang et al, 2019). FR (700-800 nm) was an influence on the size of leaves, total leaf area of geranium and snapdragon by 7%.…”
Section: Holy Basilmentioning
confidence: 87%
See 3 more Smart Citations